Analisis Manajemen Strategis pada PDAM Surya Sembada Kota Surabaya - Endri Haryati; Agus Purbo Widodo; Gogi Kurniawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Management is a series of processes that include planning, organizing, implementing, supervising, evaluating and controlling activities in order to empower all organizational/company resources, both human resource capital, financial capital, materials (land, natural resources or raw materials), and technology optimally to achieve organizational/company goals. A grand strategy is a general plan consisting of major steps taken by a company to achieve long-term goals. There are three types of grand strategies, namely growth, diversification, stability, and retrenchment. In their efforts to survive, develop, and make a profit, entrepreneurs carry out a marketing mix. Marketers can use a service marketing mix, which is an evolution of the goods marketing mix, to determine the service features they will offer to customers. Marketing includes actions that are useful for creating, developing, and distributing goods made according to the demands of prospective buyers based on the ability to make goods. PDAM Surya Sembada Surabaya, based in Surabaya, East Java, is one of the most reliable and leading regional drinking water companies in Indonesia to date. This company has been established since 1976 and is owned by the Surabaya City Government. The strategy creation at PDAM Surya Sembada Surabaya, in the form of a discount on the cost of installing new house line connections applies to all groups of household customers, including business customers, real estate customers, general social customers, and special social customers. Pipe renewal is a product. PDAM wants to replace or repair pipes that are currently operating. This must be done because the current pipes have been operating since 1980. PDAM Surya Sembada wants to keep up with the times by launching a Network Product—Customer Information Service (CIS). With CIS, the people of Surabaya can carry out administrative activities related to water affairs such as recording meters, filing complaints, and adding new lists without having to come to the PDAM office. PDAM Surya Sembada wants to keep up with the times by launching a Network Product—Customer Information Service (CIS). With CIS, the people of Surabaya can carry out administrative activities related to water affairs such as recording meters, filing complaints, and adding new lists without having to come to the PDAM office.